The Creative and Reflective Professor in the Global Pandemic of Covid - Innovative Learning Design for Present and Future: Array - Popa, Doinița (Acta Universitatis Danubius. Relationes Internationales, 2022)
The paper aims to address how the transition from classical to digital education has been due to the global pandemic of covid, the speed with which the teachers have identified the most effective methods of adaptation to translate the process into a new form of teaching- learning-evaluation, with its limits or advantages, as well as what the school will become after the pandemic crises. Teachers have reinvented themselves, and digital teaching has brought the most innovative techniques and learning methods, which, of course, outline a new profile of the modern teacher, forced to change the rules during the game, sometimes reaching unsuspected performance. Also, the extensive studies and research done so far on education systems reveal essential issues that could be considered starting points for what could become the educational path in the future. Thus, this paper talk about a reconsideration of the concept of universal learning design through the diversity of innovative techniques and methods valued and adapted to the current context.